AN ANALYSIS OF LANGUAGE SHIFT IN JAVA LANGUAGE IN MEDAN - Rafika Purba (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2013)
Abstract The research deals of language shift. the problems of this study are What factors that make language shift occurs in Java community members in Medan and Why does language shift occur in Java community members in Medan. The objectives of the study are to find out what factors make language shift occurs in Java community members in Medan and to find out why language shift occurs in Java community in Medan. the study is considered to enrich the theories in language planning especially about Java language shift in Medan, factors influence java language in Medan, reasons of the Javanese people shifts into Indonesian language in Medan. The method of collecting data for this research is qualitative research design with a single case study to get the understanding on this study. the research can claim that Java language shift is influenced by bilingualism, migration, and economic, value and attitude factor and reason of the Java language shift into Indonesian language is the status Indonesian language. Keywords : Languge shift, Java language